Diverse Virulent Pneumophages Infect Streptococcus mitis - Ouennane, Siham (Public Library of Science, 2015)

(untitled) (PLoS One)
Streptococcus mitis has emerged as one of the leading causes of bacterial endocarditis and is related to Streptococcus pneumoniae. Antibiotic resistance has also increased among strains of S. mitis and S. pneumoniae. Phages are being reinvestigated as alternatives to antibiotics for managing infections. In this study, the two virulent phages Cp-1 (Podoviridae) and Dp-1 (Siphoviridae), previously isolated from S. pneumoniae, were found to also infect S. mitis. Microbiological assays showed that both pneumophages could not only replicate in S. mitis but also produced more visible plaques on this host. However, the burst size and phage adsorption data were lower in S. mitis as compared to S. pneumoniae. A comparison of the genomes of each phage grown on both hosts produced identical nucleotide sequences, confirming that the same phages infect both bacterial species. We also discovered that the genomic sequence of podophage Cp-1 of the Félix d’Hérelle collection is different than the previously reported sequence and thus renamed SOCP.